Assessing the challenges of Fourier transform infrared spectroscopic analysis of blood serum. Issue 3 (31st January 2014) - Hughes, Caryn; Brown, Michael; Clemens, Graeme; Henderson, Alex; Monjardez, Geraldine; Clarke, Noel W.; Gardner, Peter
Abstract: There are many approaches to measuring the infrared spectrum of a blood serum sample. Naturally, each approach will have both advantages and disadvantages. We report on the progress of the application of infrared spectroscopy in the field of blood serum analysis towards clinical application, with a focus on prostate cancer. In order to perform a high‐powered study with clinical relevance, choosing the most suitable approach must undergo careful consideration. We review the possibilities of using different sample preparation methods and speculate upon the potential pitfalls of both transmission and attenuated total reflectance (ATR) techniques. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)